Optimization of core–valence states of molecules. (17th January 2017) - Valiev, R. R.; Eland, J. H. D.; Feifel, R.; Ågren, H.
ABSTRACT: Core–valence double-electron ionisation spectra of a few small molecules – carbon monoxide, ammonia, methyl fluoride and thiophene – are presented and analysed using the self-consistent field algorithm introduced by Hans Jørgen Jensen 30 years ago. It confirms the utility of this algorithm, frequently employed to obtain stable and sharp convergence of wave functions for the benefit of calculations of a great variety of molecular properties, thus also for optimisation of core–valence states and for the interpretation of the corresponding spectra. Abstract :